Research Progress on Benzimidazole Fungicides: A Review - Song Bai; Miaohe Zhang; Shouying Tang; Miao Li; Rong Wu; Suran Wan; Lijun Chen; Xian Wei; Feifei Li (Molecules, 2024)
Benzimidazole fungicides are a class of highly effective, low-toxicity, systemic broad-spectrum fungicides developed in the 1960s and 1970s, based on the fungicidal activity of the benzimidazole ring structure. They exhibit biological activities including anticancer, antibacterial, and antiparasitic effects. Due to their particularly outstanding antibacterial properties, they are widely used in agriculture to prevent and control various plant diseases caused by fungi. The main products of benzimidazole fungicides include benomyl, carbendazim, thiabendazole, albendazole, thiophanate, thiophanate-methyl, fuberidazole, methyl (1-{[(5-cyanopentyl)amino]carbonyl}-1H-benzimidazol-2-yl) carbamate, and carbendazim salicylate. This article mainly reviews the physicochemical properties, toxicological properties, disease control efficacy, and pesticide residue and detection technologies of the aforementioned nine benzimidazole fungicides and their main metabolite (2-aminobenzimidazole). On this basis, a brief outlook on the future research directions of benzimidazole fungicides is presented.